Evidence for radio and X-ray auroral emissions from the magnetic B-type star ρ Oph A. Issue 4 (28th February 2020) - Leto, P; Trigilio, C; Leone, F; Pillitteri, I; Buemi, C S; Fossati, L; Cavallaro, F; Oskinova, L M; Ignace, R; Krtička, J; Umana, G; Catanzaro, G; et al.
Abstract: We present new ATCA multiwavelength radio measurements (range 2.1–21.2 GHz) of the early-type magnetic star ρ Oph A, performed in 2019 March during three different observing sessions. These new ATCA observations evidence a clear rotational modulation of the stellar radio emission and the detection of coherent auroral radio emission from ρ Oph A at 2.1 GHz. We collected high-resolution optical spectra of ρ Oph A acquired by several instruments over a time span of about 10 yr. We also report new magnetic field measurements of ρ Oph A that, together with the radio light curves and the temporal variation of the equivalent width of the He i line (λ = 5015 Å), were used to constrain the rotation period and the stellar magnetic field geometry. The above results have been used to model the stellar radio emission, modelling that allowed us to constrain the physical condition of ρ Oph A's magnetosphere. Past XMM–Newton measurements showed periodic X-ray pulses from ρ Oph A. We correlate the X-ray light curve with the magnetic field geometry of ρ Oph A. The already published XMM–Newton data have been re-analysed showing that the X-ray spectra of ρ Oph A are compatible with the presence of a non-thermal X-ray component. We discuss a scenario where the emission phenomena occurring at the extremes of the electromagnetic spectrum, radio and X-ray, are directly induced by the same plasma process. We interpret the observed X-ray and radio features of ρ Oph A as having an auroral origin.